Antibacterial Activity of Methanol Extract of Red Dragon Fruit Peel ( Hylocereus polyrhizus) against MethicillinSusceptible Staphylococcus aureus ( MSSA) ATCC 25923 and Methicillin Resistant Staphylococcus aureus (MRSA) In Vitro - Shazia Hafazhah Aulia; Yuani Setiawati; Eko Budi Koendhori (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Staphylococcus aureus is one of the most virulent Staphylococcus which could cause systemic broad-spectrum infections and developed resistant strains. Red dragon fruit (Hylocereus polyrhizus) peel has a broad antibacterial activity against both gram-negative and positive bacteria, including Staphylococcus aureus. Objective: To determine and compare the antibacterial activity of methanol extract of red dragon fruit peel against Methicillin-Susceptible Staphylococcus aureus ATCC 25923 and Methicillin-Resistant Staphylococcus aureus. Method: Well diffusion test method was performed on 5 concentrations: 100%, 75%, 50%, 25%, and 0%, dissolved in DMSO 10% where at a concentration of 100% contains 1g/mL extract. The inhibition zone elicited as clear zone around the well then measured and analyzed with SPSS using One-Way ANOVA and Post Hoc LSD, to determine the significance of each concentration. Results: The mean diameter of the inhibition zone observed towards Methicillin-Susceptible Staphylococcus aureuswas 9.5333 ± 0.26822 - 15.4167 ± 0.22048, while bigger zone was found in Mueller-Hinton plate with Methicillin-Resistant Staphylococcus aureus which is 12.30 ± 0.20817 - 17.80 ± 0.25166 mm. Conclusion: This study showed that methanol extract of red dragon fruit peel has antibacterial activity against S. aureus, and shows higher antibacterial activity against Methicillin-Resistant Staphylococcus aureus than MethicillinSusceptible Staphylococcus aureus.